2018
DOI: 10.1007/s00018-018-2800-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atypical mitochondrial cyclic-AMP level in nephropathic cystinosis

Abstract: Nephropathic cystinosis (NC) is a rare disease caused by mutations in the CTNS gene encoding for cystinosin, a lysosomal transmembrane cystine/H symporter, which promotes the efflux of cystine from lysosomes to cytosol. NC is the most frequent cause of Fanconi syndrome (FS) in young children, the molecular basis of which is not well established. Proximal tubular cells have very high metabolic rate due to the active transport of many solutes. Not surprisingly, mitochondrial disorders are often characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 59 publications
2
28
0
1
Order By: Relevance
“…These findings are consistent with data showing that an increase of parkin expression results in mitochondrial fragmentation [36] and is associated with MFN2 ubiquitination [37]. In addition, the increase of FIS1, in cystinotic cell, might be due to Sirt3 protein [38] that was found downregulated in the same cystinotic cell line [8]. OPA1, an inner mitochondrial membrane GTPase protein, has gained attention because it regulates important mitochondrial functions, including the balance between mitochondrial fusion and fission processes, the stability of the mitochondrial respiratory chain complexes, the proapoptotic release of cytochrome c molecules sequestered within the mitochondrial cristae and the maintenance of mitochondrial cristae architecture [39].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with data showing that an increase of parkin expression results in mitochondrial fragmentation [36] and is associated with MFN2 ubiquitination [37]. In addition, the increase of FIS1, in cystinotic cell, might be due to Sirt3 protein [38] that was found downregulated in the same cystinotic cell line [8]. OPA1, an inner mitochondrial membrane GTPase protein, has gained attention because it regulates important mitochondrial functions, including the balance between mitochondrial fusion and fission processes, the stability of the mitochondrial respiratory chain complexes, the proapoptotic release of cytochrome c molecules sequestered within the mitochondrial cristae and the maintenance of mitochondrial cristae architecture [39].…”
Section: Discussionsupporting
confidence: 91%
“…However, cysteamine does not correct the above cited cellular alterations and does not stop the progress of the Fanconi syndrome. Our recent studies have shown in CTNS−/− ciPTEC a higher mitochondrial fragmentation index associated with lower mitochondrial potential and mitochondrial cyclic AMP levels, rescued by 24 h treatment with 100 µM cysteamine or with the cell-permeant analogue of cyclic AMP, 8-Br-cAMP [8]. cAMP, in fact, is one of the major regulators of mitochondrial function [28][29][30] and dynamics [31].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, we exclude the possible confounding of steroid treatment in KTx recipients, while demonstrating, in a quantitative manner, the presence of a skin phenotype that points to enhanced intrinsic skin aging in cystinosis (Moloney et al, 2005;Schoepe et al, 2006). As the pathophysiology of cystinosis shares similar features associated with cellular senescence as in intrinsic skin aging, including enhanced apoptosis and impaired autophagic flux resulting in mitochondrial dysfunction and increased generation of reactive oxygen species, it is likely that these mechanisms underlie the skin phenotype (Bellomo et al, 2018;Cherqui and Courtoy, 2017;Jenkins, 2002;Levtchenko et al, 2005;Luciani et al, 2018 Figure 1. Epidermal and papillary dermis thinning is present in nonekidney-transplanted patients with cystinosis in adolescent and young adult age group as assessed by HD-OCT. (a) HD-OCT image acquisition analysis workflow.…”
mentioning
confidence: 80%
“…Mitochondrial fission is an important mechanism that precedes elimination of damaged mitochondrial by mitophagy 41 and mitochondrial fragmentation is induced by oxidative stress and has been associated with human disease. Mitochondrial dysfunction has long been demonstrated in many LSDs including cystinosis 42 . Here, to establish the impact of DYNC1LI2 reconstitution on mitochondrial fragmentation in cystinotic cells, we measured mitochondria fragmentation in wild-type and Ctns -/cells expressing DYNC1LI2 or DYNC1LI1.…”
Section: Dync1li2 Decreases Mitochondria Fragmentation and Protects Cmentioning
confidence: 99%